2010
DOI: 10.1016/j.jvs.2009.08.080
|View full text |Cite
|
Sign up to set email alerts
|

Echolucent or predominantly echolucent femoral plaques predict early restenosis after eversion carotid endarterectomy

Abstract: Objective: Although the association between vulnerable lesions and cardiovascular events is well established, little is known about their relationship to postsurgery restenosis. To address this issue, we initiated a prospective, nonrandomized study to examine the femoral plaques on both sides in patients who were undergoing eversion carotid endarterectomy (CEA) and were longitudinally followed-up for early restenosis development. Methods: The final analysis enrolled 321 patients (189 women) with a median age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Corresponding to other studies [ 30 , 31 ], we also evaluated several possible risk factors and found hyperlipidemia to be significantly more common among patients with ISR. The role of hyperlipidemia in the formation of neointimal hyperplasia has also been demonstrated by other research groups [ 32 36 ]. Hyperlipidemia increases the entry of low-density lipoprotein (LDL) into the intima and its progressive oxidative alteration in the subendothelial space.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Corresponding to other studies [ 30 , 31 ], we also evaluated several possible risk factors and found hyperlipidemia to be significantly more common among patients with ISR. The role of hyperlipidemia in the formation of neointimal hyperplasia has also been demonstrated by other research groups [ 32 36 ]. Hyperlipidemia increases the entry of low-density lipoprotein (LDL) into the intima and its progressive oxidative alteration in the subendothelial space.…”
Section: Discussionsupporting
confidence: 54%
“…Hyperlipidemia increases the entry of low-density lipoprotein (LDL) into the intima and its progressive oxidative alteration in the subendothelial space. Oxidized LDL results in further lipid infiltration across the intact endothelium, where it aggregates and activates the release of mitogens from platelets, macrophages, and endothelial cells; this, in turn, stimulates smooth muscle cell proliferation, thereby leading to neointima formation [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Innominate artery stenting protocol. The preprocedural work-up included clinical data collection (symptoms, risk factors, which were described in detail previously, 13 and medical history), radial pulse palpation and blood pressure measurement in both arms, neurologic evaluation, and duplex scan of the neck arteries. In recent years, computed tomography (CT) or magnetic resonance angiography have become part of the preprocedural imaging protocol in patients with multivessel supra-aortic disease to evaluate which lesion should be treated first.…”
Section: Methodsmentioning
confidence: 99%
“…25 The plaque surface can be defined as smooth and regular, mildly irregular, or ulcerated in the case of a variation in height between 0.4 and 2 mm on the contour of the plaque. 26 An example of ulceration in Doppler sonography is shown in Fig 3A. However, it is difficult to detect plaque ulceration by sonography due to various limitations. First, the overall accuracy of using B-mode sonography against criterion standard techniques (DSA or histopathology) is not high (sensitivity and specificity ranges from 39% to 89% and 72% to 87%, respectively).…”
Section: Sonographymentioning
confidence: 99%